Natural Polyphenols as Immunomodulators to Rescue Immune Response Homeostasis: Quercetin as a Research Model against Severe COVID-19 - Roberta Bernini; Francesca Velotti (Molecules, 2021)
The COVID-19 pandemic is caused by SARS-CoV-2 and is leading to the worst health crisis of this century. It emerged in China during late 2019 and rapidly spread all over the world, producing a broad spectrum of clinical disease severity, ranging from asymptomatic infection to death (4.3 million victims so far). Consequently, the scientific research is devoted to investigating the mechanisms of COVID-19 pathogenesis to both identify specific therapeutic drugs and develop vaccines. Although immunological mechanisms driving COVID-19 pathogenesis are still largely unknown, new understanding has emerged about the innate and adaptive immune responses elicited in SARS-CoV-2 infection, which are mainly focused on the dysregulated inflammatory response in severe COVID-19. Polyphenols are naturally occurring products with immunomodulatory activity, playing a relevant role in reducing inflammation and preventing the onset of serious chronic diseases. Mainly based on data collected before the appearance of SARS-CoV-2, polyphenols have been recently suggested as promising agents to fight COVID-19, and some clinical trials have already been approved with polyphenols to treat COVID-19. The aim of this review is to analyze and discuss the in vitro and in vivo research on the immunomodulatory activity of quercetin as a research model of polyphenols, focusing on research that addresses issues related to the dysregulated immune response in severe COVID-19. From this analysis, it emerges that although encouraging data are present, they are still insufficient to recommend polyphenols as potential immunomodulatory agents against COVID-19.